Language Learning Process and Gender Difference Implied from the Turn-Takings Used in EFL Student Conversation Club - Ilmi, Syaripa Nurul; Susilo, Susilo; Hermagustiana, Istanti (Dinamika Ilmu, 2019)
This study aims at investigating the kinds of turn-taking mostly used by EFL learners, how the turn-takings are portrayed as a process of EFL learning, and how the EFL learners differ in making their turn-takings according to their gender. This study was qualitative in nature, using 10 members of English Club of English department students, Mulawarman University as the participants. The procedures of data collecting were video-tape recording observation and semi-structure interview. The data were analyzed by using conversational analysis and percentage frequencies. The result revealed that: 1) the kinds of turn-taking mostly used by the participants were adjacency pair and insertion sequence from the sequence type of turn-taking, almost all kinds turn-taking from the overlap turn-taking except the third party mediation, and other-repair and self-repair from the repair turn-taking; 2) all members of the English Club felt they acquired  their languages as they practiced them in either written and spoken communication; and 3) the female members dominated talk than the male ones.